(untitled) (Hilo Analítico, 2022)
From the first moment we born, the society constantly requires us to do, whether to work, to study, for household chores or any other action that is seen as "productive", there is always a demand on movement and fulfillment of something. Therefore, if a person does not perform a task or duty, they are singled out and judged, where they constantly refer to these subjects as: “a lazy person”, “someone who does nothing”, “someone without vision”, “a good for nothing ", among other expressions. This being the case, one might think that it is okay to carry out a productive activity rather than do nothing.